2007
DOI: 10.1007/s00586-007-0310-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of unstable thoracolumbar junction burst fractures with short- or long-segment posterior fixation in magerl type a fractures

Abstract: The treatment of thoracolumbar fractures remains controversial. A review of the literature showed that short-segment posterior fixation (SSPF) alone led to a high incidence of implant failure and correction loss. The aim of this retrospective study was to compare the outcomes of the SS- and long-segment posterior fixation (LSPF) in unstable thoracolumbar junction burst fractures (T12-L2) in Magerl Type A fractures. The patients were divided into two groups according to the number of instrumented levels. Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
147
0
19

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(175 citation statements)
references
References 45 publications
9
147
0
19
Order By: Relevance
“…Short segment fixation of the fracture level has replaced the traditional long segment instrumentation to decrease the number of motion segments sacrificed in the fusion process [2][3][4][5]. However, when there is significant disruption of the load-sharing anterior column, the simple one level above and one level below short segment fixation does not ensure adequate stability, resulting in poor reduction in the kyphotic deformity and occurrence of instrument failure [6].…”
Section: Introductionmentioning
confidence: 99%
“…Short segment fixation of the fracture level has replaced the traditional long segment instrumentation to decrease the number of motion segments sacrificed in the fusion process [2][3][4][5]. However, when there is significant disruption of the load-sharing anterior column, the simple one level above and one level below short segment fixation does not ensure adequate stability, resulting in poor reduction in the kyphotic deformity and occurrence of instrument failure [6].…”
Section: Introductionmentioning
confidence: 99%
“…2 The loss of correction and the wedging of the fractured vertebra are common findings during postoperative follow-up. 6,[20][21][22][23][24] In our study, the surgical correction observed in the immediate postoperative period was not sustained in the long term. Like Palmisani et al, 7 we believe that the structure of the polyaxial pedicle screws contributes to this loss of correction.…”
Section: Discussionmentioning
confidence: 90%
“…6,12,13 Estamos de acordo com Palmisani et al 7 que o grande responsável por essa perda seria a utilização de parafusos poliaxiais e que, por essa razão, haverá espaço para a utilização de parafusos monoaxiais.…”
Section: Discussionunclassified